AlGaAs Tunnel Junction (TJ)-VCSELs: A NEGF–Drift-Diffusion Approach - Alberto Gullino; Valerio Torrelli; Martino D'Alessandro; Alberto Tibaldi; Francesco Bertazzi; Michele Goano; Pierluigi Debernardi (IEEE Photonics Journal)
This work reports a multiscale physics-based approach aimed at investigating the benefits of introducing a single tunnel junction (TJ) within conventional AlGaAs Vertical-Cavity Surface-Emitting Lasers (VCSELs). Our comprehensive VCSEL solver VENUS is augmented with a non-equilibrium Green's function (NEGF) approach to extract the band-to-band tunneling rate across the TJ. To showcase the NEGF-VENUS features, we apply it to the commercial pin oxide confined AlGaAs VCSEL previously investigated by VENUS, by inserting a TJ with minimal variations to the optical resonator. Besides finding the optimal position of TJ and oxide aperture, we can also compare the different hole injection schemes in the active region. Our results show the potential of doubling the maximum output power with the same threshold current, with perspectives of further enhancement by stacking more tunnel junctions.